2010
DOI: 10.1007/s12012-010-9091-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardioprotective and Cardiotoxic Effects of Bilberry Anthocyanins in Ischemia–Reperfusion Injury: Beyond Concentration-Dependent Antioxidant Activity

Abstract: Despite being reported to reduce the risk of cardiovascular diseases, little is known about acute direct effects of bilberry anthocyanins on whole mammalian heart under ischemia-reperfusion (I-R) conditions. Bilberry anthocyanins were prepared from the ripe bilberries and analyzed using HPLC-DAD. Their antioxidant activity was evaluated by measuring the intrinsic free radical-scavenging capacity and by cellular antioxidant assay (CAA) on endothelial cells, where we quantified the intracellular capacity to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 38 publications
1
45
1
1
Order By: Relevance
“…Recently, increased attention has been given to the possible health benefits of these compounds in preventing chronic and degenerative diseases incluiding heart disease and cancer (Lim et al, 2011; Ziberna et al, 2010). The great abundance of this fruit in the southeast Brazil could make its fruits a promising anthocyanin-rich crop.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increased attention has been given to the possible health benefits of these compounds in preventing chronic and degenerative diseases incluiding heart disease and cancer (Lim et al, 2011; Ziberna et al, 2010). The great abundance of this fruit in the southeast Brazil could make its fruits a promising anthocyanin-rich crop.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, both antioxidant and pro-oxidant activities were reported, depending upon certain experimental conditions (Halliwell, 2008; Ziberna et al , 2010). Often these pro-oxidant effects involve interactions of phenolic compounds with transition metal ions, which can be ubiquitously found in biologic systems, or as universal contaminants of biologic reagents (Halliwell, 2009).…”
Section: Potential Dual Mode Of Action Of Phenolic Compoundsmentioning
confidence: 99%
“…A large number of studies have identified cellular targets that could be involved in the health promoting actions of dietary plant phenolic compounds. Epidemiological evidence indicates that diets rich in fruits and vegetables promote health and attenuate or delay the onset of many diseases (Knekt et al , 2002; Ghosh & Konishi, 2007; Rhone & Basu, 2008; Patil et al , 2009; Agte & Tarwadi, 2010; Cvorovic et al , 2010; Crozier et al , 2010; Ziberna et al , 2010; Kalt et al , 2010). The beneficial effects of fruits and vegetables have been largely ascribed to phenolic compounds, since ingestion of foods rich in these substances has been associated in humans and experimental animals with reduction in: i) dyslipidemia and atherosclerosis; ii) endothelial dysfunction and hypertension; iii) platelet activation and thrombosis; iv) inflammatory processes associated with induction and perpetuation of cardiovascular diseases (Fraga et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, however, no reports have demonstrated adverse effects of C3G. However, one study by Ziberna et al (2010) reported cardiotoxic effects of relatively high concentrations of anthocyanins extracted from bilberry fruit [43]. It was shown that at concentrations of 0.1~5µg/ml, anthocyanins extracted from bilberries conferred cardioprotective effects against ischemia-reperfusion injury in isolated rat hearts.…”
Section: Discussionmentioning
confidence: 99%